2016
DOI: 10.1186/s13058-016-0712-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell metabolism

Abstract: Cancer is now viewed as a stem cell disease. There is still no consensus on the metabolic characteristics of cancer stem cells, with several studies indicating that they are mainly glycolytic and others pointing instead to mitochondrial metabolism as their principal source of energy. Cancer stem cells also seem to adapt their metabolism to microenvironmental changes by conveniently shifting energy production from one pathway to another, or by acquiring intermediate metabolic phenotypes. Determining the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
349
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(368 citation statements)
references
References 97 publications
5
349
0
1
Order By: Relevance
“…Although much is known regarding metabolic pathways important for tumour survival, the potential for therapeutic metabolic alteration of CSCs still remains under investigation [35, 36]. Recent studies indicate that CSCs have different metabolic properties when compared to the tumour bulk.…”
Section: Cscs and Their Metabolic Alterationsmentioning
confidence: 99%
“…Although much is known regarding metabolic pathways important for tumour survival, the potential for therapeutic metabolic alteration of CSCs still remains under investigation [35, 36]. Recent studies indicate that CSCs have different metabolic properties when compared to the tumour bulk.…”
Section: Cscs and Their Metabolic Alterationsmentioning
confidence: 99%
“…[64] In contrast, other studies on pancreatic and other breast cancer cell lines reported increased mitochondrial respiration in the CSC population. [65] This may be linked to CSCs rewiring their metabolic states depending on the surrounding cellular environment. Furthermore, different types of tumors may contain CSCs exhibiting different underlying metabolic features.…”
Section: Targeting the Metabolic State Of Cscs: Mitochondrial Metabolmentioning
confidence: 99%
“…To functionally enrich for CSCs, the entire cell population can be trypsinized and seeded as a single-cell suspension onto low-attachment plates [1,2]. Under these conditions, the majority of “bulk” cancer cells die (> 90%) via apoptosis, while only the CSCs survive and propagate, ultimately resulting after 5 d in the formation of 3D spheroid structures.…”
Section: Mitochondrial Function Is Required For Csc Propagationmentioning
confidence: 99%